1993
DOI: 10.1287/mnsc.39.7.845
|View full text |Cite
|
Sign up to set email alerts
|

Massaging Mean-Variance Inputs: Returns from Alternative Global Investment Strategies in the 1980s

Abstract: This paper explores the impact of adjustments to the inputs on total returns, terminal wealth, and portfolio turnover in an unconstrained monthly mean-variance (MV) asset allocation over time. It is well known that MV allocations are very sensitive to small forecast errors in the means and covariances. This sensitivity is especially pronounced for errors in means. One way to control this sensitivity to forecast errors is to use Stein estimation. We examined three naive applications of Stein estimation for six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(31 citation statements)
references
References 21 publications
1
30
0
Order By: Relevance
“…7 In addition to models that try to maximize the Sharpe ratio, we employ several models that aim at constructing minimum variance portfolios, thereby ignoring information about sample mean returns. The superior performance of minimum variance optimization has been demonstrated in various studies, which mostly concentrate on stock markets (e.g., Haugen and Baker, 1991;Chopra et al, 1993;and Jagannathan and Ma, 2003).…”
Section: Please Insert Table 2 Herementioning
confidence: 99%
“…7 In addition to models that try to maximize the Sharpe ratio, we employ several models that aim at constructing minimum variance portfolios, thereby ignoring information about sample mean returns. The superior performance of minimum variance optimization has been demonstrated in various studies, which mostly concentrate on stock markets (e.g., Haugen and Baker, 1991;Chopra et al, 1993;and Jagannathan and Ma, 2003).…”
Section: Please Insert Table 2 Herementioning
confidence: 99%
“…These estimation difficulties are by now well documented; early studies are Cohen and Pogue (1967); Frankfurter et al (1971), see also Jobson and Korkie (1980); Jorion (1985Jorion ( , 1986; Best and Grauer (1991); Chopra et al (1993); Board and Sutcliffe (1994). Brandt (forthcoming) gives a very good overview.…”
Section: Introductionmentioning
confidence: 97%
“…Let μ be a vector of expected returns for each of N stocks, and let Σ be an N × N covariance matrix for the returns. The problem can be written as Even though these optimization problems play a central role in a modern portfolio theory, it has been observed that the solutions are very sensitive to their input parameters [3,5,6,7]. Thus, in order to construct a good portfolio using these formulations, the covariance matrix Σ must be well estimated.…”
Section: Introductionmentioning
confidence: 99%